Presence of SNPs in IL6 and IL6R and its relation with obesity (Research, Society and Development, 2024)
Obesity is a chronic disease that results from environmental and genetic mechanisms that may be related to SNPs (Single Nucleotide Polymorphism) in specific genes linked to this condition. This occurs due to the establishment of a chronic inflammation framework according to each phenotype. One of the main cytokines involved in this process is Interleukin 6 (IL-6), located on chromosome 7p21. Another gene involved, IL6R, which encodes the IL-6 receptor is located on chromosome 1q21. This cytokine inhibits adiponectin expression, as well as, insulin receptors and signaling, which makes it have an activity on body weight, energy homeostasis and insulin resistance. This article aims to describe the gene's action in obesogenesis and list the main SNPs, as well as their frequency through a integrative literature review. The main SNPs listed were rs2069845, rs2069849, rs1800795 and rs1800797 as risk factors for central obesity, metabolic syndrome and diabetes. And the SNPs of the receptor gene were rs7514452, rs10752641, rs2228145 and rs8192284. Considering that the IL-6 gene has its mechanism connected to the adiponectin and insulin signaling mechanisms, its participation in the construction of the obesity picture is verified, in which there is a decrease in adiponectin and an increase in IR, which is an essential factor for fat deposition and adipocyte formation, thus leading to obesity when this gene is deregulated by the presence of SNPs.